2020
DOI: 10.1016/j.jaccas.2020.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Constrictive Pericarditis After Lung Transplantation

Abstract: As a rare complication after lung transplant, cardiac constriction should not be missed. Physical exam, echocardiography, and catheterization are essential for diagnosis A 65-year-old man with previous coronary artery disease and idiopathic pulmonary fibrosis underwent bilateral lung transplant and subsequently presented for progressive dyspnea and volume overload. Cardiac imaging and cardiac catheterization confirmed constriction, and complete pericardiectomy was performed. The patient had rapid resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Logan et al. ( 3 ) present a case that highlights diagnostic dilemmas, appropriate testing, and ultimately successful surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Logan et al. ( 3 ) present a case that highlights diagnostic dilemmas, appropriate testing, and ultimately successful surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of JACC: Case Reports, Logan et al. ( 3 ) describe an interesting case of a 65-year-old man with idiopathic pulmonary fibrosis who underwent bilateral lung transplantation complicated by new onset heart failure. After considering a broad differential and performing extensive workup, the investigators concluded that the most likely etiology was constrictive pericarditis.…”
mentioning
confidence: 99%
See 3 more Smart Citations